2014
DOI: 10.1063/1.4892664
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature multiferroicity in orthorhombic LuFeO3

Abstract: From the measurement of dielectric, ferroelectric, and magnetic properties we observe simultaneous ferroelectric and magnetic transitions around ∼600 K in orthorhombic LuFeO 3 . We also observe suppression of the remanent polarization by ∼95% under a magnetic field of ∼15 kOe at room temperature. The extent of suppression of the polarization under magnetic field increases monotonically with the field. These results show that even the orthorhombic LuFeO 3 is a room temperature multiferroic of type-II variety ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 18 publications
4
38
0
Order By: Relevance
“…The anomaly of the intrinsic dielectric response was observed in [3] near the magnetic transition point T N~6 00 K that clearly told about a coupling between dielectric and magnetic properties in o-LuFeO 3 . In our case this anomaly has corresponded to the observed increase of ε' with increasing temperature up to 450 K. We also observed a frequency dependent maximum of permittivity near 130 K. Similar low temperature anomaly, indicating possible charge ordering in the temperature range of 150-300 K, was observed in o-LuFeO 3 ceramics in [9], assuming the preserving of the dielectric properties during the transition from bulk samples to thin films how it was in the case of magnetic properties.…”
Section: Magnetization and Magnetic Susceptibilitymentioning
confidence: 97%
See 3 more Smart Citations
“…The anomaly of the intrinsic dielectric response was observed in [3] near the magnetic transition point T N~6 00 K that clearly told about a coupling between dielectric and magnetic properties in o-LuFeO 3 . In our case this anomaly has corresponded to the observed increase of ε' with increasing temperature up to 450 K. We also observed a frequency dependent maximum of permittivity near 130 K. Similar low temperature anomaly, indicating possible charge ordering in the temperature range of 150-300 K, was observed in o-LuFeO 3 ceramics in [9], assuming the preserving of the dielectric properties during the transition from bulk samples to thin films how it was in the case of magnetic properties.…”
Section: Magnetization and Magnetic Susceptibilitymentioning
confidence: 97%
“…Ferroelectricity transition in h-LuFeO 3 was observed below T C = 1050 K connecting from a P6 3 /mmc → P6 3 cm structure distortion [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The LFO, which is one of the rare-earth orthoferrites, has been considered to be potential multiferroics [19,20]. Nevertheless, it has been reported that the LFO thin films showed very low ferroelectric polarizations [20][21][22].…”
Section: Introductionmentioning
confidence: 98%